Atomic structure, electronic structure and optical absorption of inorganic perovskite compounds Cs2SnI6-nXn (X = F, Cl, br; n = 0 ∼ 6): A first-principles study. (October 2022) - Xia, Du; Xuan, Wang; Nairui, Xiao; Yehua, Tang; Chengxiao, Peng; Ke-Fan, Wang
Highlights: Mean lattice constant, weighted sn-X and Cs-X bond length decreases linearly with n ; Bond length of each sn-X bond diminishes slightly in sn-X octahedral structure; Eg of Cs2 SnI6-n Xn increases nonlinearly with the number of the alloyed X - ions; Eleven Cs2 SnI6-n Xn with Eg between 1.0 eV and 2.0 eV all have a direct bandgap; At some doping levels, the Cs2 SnI6-n Xn alloys can have a much lower hole effective mass. Abstract: As a possible alternative to organic–inorganic hybrid perovskite halide, inorganic Cs2 SnI6 has drawn more and more research attention recently. In order to find more Cs2 SnI6 derivatives as the potential solar cell absorber materials, I - ions in Cs2 SnI6 are replaced by other halogen ions and forms the Cs2 SnI6-n Xn (X = F, Cl, Br; n = 1 ∼ 6) compounds, whose atomic structures, electronic structures and optical absorption are investigated by first principles calculations. When the alloying level n increases, the mean lattice constants, the weighted sn-X and Cs-X bond lengths all decreases linearly; the bond length of each sn-X diminishes slightly inside the octahedral structure; Eg of Cs2 SnI6-n Xn increases nonlinearly. Eleven Cs2 SnI6-n Xn compounds have an Eg between 1.0 eV and 2.0 eV and so can be potentially used as the light absorption layer of solar cells. Their partial DOS demonstrate that as the alloying level n increases, I 5p orbital in VBM and CBM is gradually substituted by Br 4p, or Cl 3p, or F 2p orbital. The eleven Cs2 SnI6-n Xn alloys all have a direct bandgap although the lattice distortion induced by the alloyed X - ion. At some doping levels, the Cs2 SnI6-n Xn alloys can have a much lower m*h and thus promise a better photovoltaic performance than that of Cs2 SnI6 .